The book of homilies : a critical edition - Bray, Gerald Lewis (Cambridge, United Kingdom : James Clarke & Co, 2015)
The two Books of Homilies, along with the Book of Common Prayer and the Ordinal, have long been basic documents of the Church of England, and are valuable in showing how Anglican doctrine shifted during the Reformation, as well as being of considerable historical importance. The first book, published in 1547, early in the reign of Edward VI, was partly, though not entirely, the work of Archbishop Thomas Cranmer, and the inspiration appears to have been his. This was intended to raise the standards of preaching by offering model sermons covering particular doctrinal and pastoral themes, either to be read (particularly by unlicensed clergy) or to provide preachers with additional material for their own sermons. The success of the venture led Bishop Edmund Bonner, who had contributed to Cranmer's book, to produce his own Book of Homilies in 1555, during the reign of Queen Mary. The Second Book of Homilies, published in 1563 (and in a revised form in 1571) appears in turn to have been influenced by both Cranmer's and Bonner's books. The present edition brings together all three books, edited and introduced by Revd Dr Gerald Bray.
The first book of homilies -- Bishop Bonner's homilies -- The second book of homilies.
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 610
Keywords: Church of England -- Sermons; Church of England -- Sermons -- Early works to 1800.; Church of England; Sermons, English -- 16th century; RELIGION -- Sermons -- Christian; Sermons, English; 1500-1599; Electronic books; Sermons